(4y+3x-11)dx+(2x+y-5)dy=0

Simple and best practice solution for (4y+3x-11)dx+(2x+y-5)dy=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4y+3x-11)dx+(2x+y-5)dy=0 equation:


Simplifying
(4y + 3x + -11) * dx + (2x + y + -5) * dy = 0

Reorder the terms:
(-11 + 3x + 4y) * dx + (2x + y + -5) * dy = 0

Reorder the terms for easier multiplication:
dx(-11 + 3x + 4y) + (2x + y + -5) * dy = 0
(-11 * dx + 3x * dx + 4y * dx) + (2x + y + -5) * dy = 0

Reorder the terms:
(-11dx + 4dxy + 3dx2) + (2x + y + -5) * dy = 0
(-11dx + 4dxy + 3dx2) + (2x + y + -5) * dy = 0

Reorder the terms:
-11dx + 4dxy + 3dx2 + (-5 + 2x + y) * dy = 0

Reorder the terms for easier multiplication:
-11dx + 4dxy + 3dx2 + dy(-5 + 2x + y) = 0
-11dx + 4dxy + 3dx2 + (-5 * dy + 2x * dy + y * dy) = 0

Reorder the terms:
-11dx + 4dxy + 3dx2 + (2dxy + -5dy + dy2) = 0
-11dx + 4dxy + 3dx2 + (2dxy + -5dy + dy2) = 0

Reorder the terms:
-11dx + 4dxy + 2dxy + 3dx2 + -5dy + dy2 = 0

Combine like terms: 4dxy + 2dxy = 6dxy
-11dx + 6dxy + 3dx2 + -5dy + dy2 = 0

Solving
-11dx + 6dxy + 3dx2 + -5dy + dy2 = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'd'.
d(-11x + 6xy + 3x2 + -5y + y2) = 0

Subproblem 1

Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0

Subproblem 2

Set the factor '(-11x + 6xy + 3x2 + -5y + y2)' equal to zero and attempt to solve: Simplifying -11x + 6xy + 3x2 + -5y + y2 = 0 Solving -11x + 6xy + 3x2 + -5y + y2 = 0 Move all terms containing d to the left, all other terms to the right. Add '11x' to each side of the equation. -11x + 6xy + 3x2 + -5y + 11x + y2 = 0 + 11x Reorder the terms: -11x + 11x + 6xy + 3x2 + -5y + y2 = 0 + 11x Combine like terms: -11x + 11x = 0 0 + 6xy + 3x2 + -5y + y2 = 0 + 11x 6xy + 3x2 + -5y + y2 = 0 + 11x Remove the zero: 6xy + 3x2 + -5y + y2 = 11x Add '-6xy' to each side of the equation. 6xy + 3x2 + -5y + -6xy + y2 = 11x + -6xy Reorder the terms: 6xy + -6xy + 3x2 + -5y + y2 = 11x + -6xy Combine like terms: 6xy + -6xy = 0 0 + 3x2 + -5y + y2 = 11x + -6xy 3x2 + -5y + y2 = 11x + -6xy Add '-3x2' to each side of the equation. 3x2 + -5y + -3x2 + y2 = 11x + -6xy + -3x2 Reorder the terms: 3x2 + -3x2 + -5y + y2 = 11x + -6xy + -3x2 Combine like terms: 3x2 + -3x2 = 0 0 + -5y + y2 = 11x + -6xy + -3x2 -5y + y2 = 11x + -6xy + -3x2 Add '5y' to each side of the equation. -5y + 5y + y2 = 11x + -6xy + -3x2 + 5y Combine like terms: -5y + 5y = 0 0 + y2 = 11x + -6xy + -3x2 + 5y y2 = 11x + -6xy + -3x2 + 5y Add '-1y2' to each side of the equation. y2 + -1y2 = 11x + -6xy + -3x2 + 5y + -1y2 Combine like terms: y2 + -1y2 = 0 0 = 11x + -6xy + -3x2 + 5y + -1y2 Simplifying 0 = 11x + -6xy + -3x2 + 5y + -1y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

d = {0}

See similar equations:

| (j-1)(-3)= | | 1.7+7.6=9.5-4x | | 2=-9+y | | 5-(4x-3)=16 | | 2x+9-4x=-7+2x | | 0=-9+y | | 8x=90+x | | 12+k-2=5k-2k | | 10-(x-4)=45 | | -5(-8m+1)=-5+3m | | 7x+3-6x=8-30 | | -2=-9+y | | -7-x= | | 12x-96=0 | | (10X+6)-(5X+4)= | | (90-x)=5(180-x)-10 | | c-7=9 | | .5(8n-14)= | | 3(x+2)+6=36 | | 14-2z=16 | | 8p-(6pg+4p)= | | -4=-9+y | | log(7x+3)=4 | | 100a+100a= | | 4(2/3h-3)= | | 21x^2-32x-5=0 | | 12x+14= | | 2j-6=3j | | 9x-3y=-2 | | 5x-2(x+3)=7(x+2) | | 8(x^2+16)=9 | | 10(15-6z)= |

Equations solver categories